Recognition of DNA Supercoil Handedness during Catenation Catalyzed by Type II Topoisomerases - Dalvie, Esha D.; Stacy, Jordan C.; Neuman, Keir C.; Osheroff, Neil (Biochemistry (Easton), 2022)
Although the presence of catenanes (i.e., intermolecular tangles) in chromosomal DNA stabilizes interactions between daughter chromosomes, a lack of resolution can have serious consequences for genomic stability. In all species, from bacteria to humans, type II topoisomerases are the enzymes primarily responsible for catenating/decatenating DNA. DNA topology has a profound influence on the rate at which these enzymes alter the superhelical state of the double helix. Therefore, the effect of supercoil handedness on the ability of human topoisomerase IIα and topoisomerase IIβ and bacterial topoisomerase IV to catenate DNA was examined. Topoisomerase IIα preferentially catenated negatively supercoiled over positively supercoiled substrates. This is opposite to its preference for relaxing (i.e., removing supercoils from) DNA and may prevent the enzyme from tangling the double helix ahead of replication forks and transcription complexes. The ability of topoisomerase IIα to recognize DNA supercoil handedness during catenation resides in its C-terminal domain. In contrast to topoisomerase IIα, topoisomerase IIβ displayed little ability to distinguish DNA geometry during catenation. Topoisomerase IV from three bacterial species preferentially catenated positively supercoiled substrates. This may not be an issue, as these enzymes work primarily behind replication forks. Finally, topoisomerase IIα and topoisomerase IV maintain lower levels of covalent enzyme-cleaved DNA intermediates with catenated over monomeric DNA. This allows these enzymes to perform their cellular functions in a safer manner, as catenated daughter chromosomes may be subject to stress generated by the mitotic spindle that could lead to irreversible DNA cleavage.